Integrated metabolomic and transcriptomic analyses reveal molecular response of anthocyanins biosynthesis in perilla to light intensity - Xie, Guanwen; Zou, Xiuzai; Liang, Zishan; Wu, Duan; He, Jiankuang; Xie, Kaicheng; Jin, Honglei; Wang, Hongbin; Shen, Qi (Frontiers in Plant Science, 2022)
The perilla anthocyanins have important medicinal and ornamental value, and their contents are significantly affected by light intensity. In view of their molecular mechanisms were not well understood, we integrated the metabolomic and transcriptomic analyses of the light-sensitive perilla variety under different light intensity. The perilla leave color were obviously affected under different treatments. Totally 140 flavonoid metabolites and 2461 genes showed steady change, among which 60 flavonoid metabolites were increased accumulation and 983 genes were upregulated expression under elevated light intensity treatment. Light treatment prominently affected the expression of genes involved in the main anthocyanin metabolites accumulation in perilla leaves. Using WGCNA analysis, we identified 4 key genes in anthocyanin biosynthesis pathway (CHI, DFR and ANS) and 147 transcription factors (MYB, bHLH, bZIP, ERF and NAC) involved in malonylshisonin biosynthesis. Among them, 6 MYBs and 4 bZIPs were predicted to play important roles in light regulation of malonylshisonin biosynthesis based on phylogenetic construction, correlation analysis, cis-acting element identification and qPCR verification. The identified key genes and regulatory factors will help us to understand the potential mechanism of photo-regulated anthocyanin accumulation in perilla.